Characterization of two multidrug-resistant Klebsiella pneumoniae harboring tigecycline-resistant gene tet(X4) in China - Yang, Yanxian; He, Ruowen; Wu, Yiping; Qin, Mingyang; Chen, Jieyun; Feng, Yu; Zhao, Runping; Xu, Lei; Guo, Xilong; Tian, Guo-Bao; Dai, Min; Yan, Bin; et al. (Frontiers in Microbiology, 2023)
Abstract Objectives: Tigecycline is recognized as one of the last-line antibiotics to treat serious bacterial infection caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). The plasmid-borne gene tet(X4) mediates high resistance to tigecycline. However, the prevalence and genetic context of tet(X4) in K. pneumoniae from various sources are not fully understood. Here, we investigated the prevalence of tet(X4)-positive K. pneumoniae and characterized the genetic context of tet(X4)-bearing plasmids in K. pneumoniae isolates. Methods: Polymerase chain reaction (PCR) was used to detect the tet(X4) gene. The transferability of the tet(X4)-carrying plasmids was tested by conjugation assays. The Galleria mellonella infection model was used to test virulence of tet(X4)-positive strains. Whole-genome sequencing and genome-wide analysis were performed to identify the antimicrobial resistance and the virulence genes, and to clarify the genetic characteristics of the tet(X4)-positive isolates. Results: Among 921 samples, we identified two tet(X4)-positive K. pneumoniae strains collected from nasal swabs of two pigs (0.22%, 2/921). The two tet(X4)-positive isolates exhibited high minimum inhibitory concentrations to tigecycline (32-256 mg/L) and tetracycline (256 mg/L). The plasmids carrying the tet(X4) gene can transfer from the donor strain K. pneumoniae to the recipient strain Escherichia coli J53. Genetic analysis of the complete sequence of two tet(X4)-carrying plasmids pTKPN_3-186k-tetX4 and pTKPN_8-216k-tetX4 disclosed that the tet(X4) gene was flanked by delta ISCR2 and IS1R, which may mediate the transmission of the tet(X4) gene. Conclusion: The prevalence of tet(X4)-positive K. pneumoniae among different sources was low. ISCR2 and IS1R may contribute to the horizontal transfer of tet(X4) gene. Effective measures should be taken to prevent the transmission of tet(X4)-producing K. pneumoniae in humans or animals.